Habilidades paternas, relacionamento conjugal e problemas de comportamento de crianças com e sem atraso no desenvolvimento - Fantinato, Aline Costa (Universidade Federal de São Carlos, 2013)
Children who don t have a positive and loving relationship with his father or whose father uses strict disciplinary practices and are exposed to violence and / or marital problems, are at a high risk to develop problems in their social development. Thus, this study aimed to: (a) compare the father s social educational skills, the characteristics of marital relationship in view of the father and behavior problems of children, between the group of children with developmental delay (G1) and the group of children who do not have developmental delay (G2) and (b) examine the relations between the variables. The study included 40 fathers who had children at preschool age (four to six years old) and their children's teachers. The research was conducted in four preschools of a small city, in the state of São Paulo, in Brazil. To reply the objectives: (a) the fathers were evaluated in relation to their repertoire of social educational skills (Parental Social Educational Skills Script Interview- RE-HSE-P) and the characteristics of the marital relationship (Marriage Questionnaire) and (b) teachers and fathers evaluated children's behaviors (Strengths & Difficulties Questionnaire - SDQ). To compare the results between groups of children s fathers, it were used the t-test and chi-square and to assess relations between variables it was used the Pearson correlation test. The results showed that fathers of children without developmental delay used the speech to express positive and negative feelings and to establish limits on the child more often compared with fathers of children with developmental delay, while the last ones emitted more inability behaviors while interacting with their children. Furthermore, fathers of children without developmental delay had better ratings in the categories evaluated in RE-HSE-P. Related to the marital relationship, it was noticed great differences in the way to describe the spouse, expression of feelings between the couple, evaluation and characteristics of the marital relationship. In most cases, the differences were positive for the group of parents of children without developmental delay. In relation to behavior problems, great differences were noted between the groups in the relationship problems with peers scale, in the teachers and fathers evaluation and in the emotional symptoms scale and in the total score of the difficulties in teachers evaluation, and the group of children with developmental delay had significantly higher scores on all scales. Overall, it was found positive correlations between fathers social educational skills and marital relationship and negative correlations between parental variables and children s behavior problems; in other words, positive educational practices and quality in the marital relationship collaborate for a good behavioral repertoire of children. These results indicate the importance of positive parental interaction with their children, as well as the quality in the marital relationship to the social development of preschool children and point directions to the need of attention to fathers of children with developmental delay. Keywords: parental involvement, social educational skills, marital conflict, behavior problems, developmental delay, preschool.
Keywords: Educação Especial; Educação participação dos pais; Habilidades sociais educativas; Relação conjugal; Problemas de comportamento; Atraso no desenvolvimento; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL